2006
DOI: 10.1361/154770206x117559
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 2024-T351 friction stir welding joints

Abstract: Characterization of macrostructure, microstructure, hardness, precipitate distribution, residual stress, and cyclic deformation behavior of 2024-T351 friction stir welded joints has been conducted. Inhomogeneous microparameters governing the nonuniform residual stresses and cyclic strength are discussed. The cyclic strength of the weld microregimes is controlled by grain size and distribution of precipitates achieved during the weld process. The comprehensive information of micro-and macromechanics is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Welding is carried out around 70-90% of the base material melting point so it is important that the tool material possess sufficient strength at these temperatures to avoid intense wear or fracture during the FSW process [5]. 3 Because of the important role played by tool geometry in process optimization of FSW, a large number of studies have been reported in the literature on the effect of tool geometry on microstructure evolution and mechanical properties [6][7][8][9][10][11][12][13][14]. Of particular interest, is the work of Fuji et al [7] on the effect of tool shape on mechanical and microstructural properties of friction stir welded 1050-H24, 6061-T6, and 5083-O aluminum plates.…”
Section: Introductionmentioning
confidence: 99%
“…Welding is carried out around 70-90% of the base material melting point so it is important that the tool material possess sufficient strength at these temperatures to avoid intense wear or fracture during the FSW process [5]. 3 Because of the important role played by tool geometry in process optimization of FSW, a large number of studies have been reported in the literature on the effect of tool geometry on microstructure evolution and mechanical properties [6][7][8][9][10][11][12][13][14]. Of particular interest, is the work of Fuji et al [7] on the effect of tool shape on mechanical and microstructural properties of friction stir welded 1050-H24, 6061-T6, and 5083-O aluminum plates.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir welding (FSW) is a type of solid state welding, invented in 1991 by The Welding Institute (TWI) in Cambridge, U.K., which involves a joining process using no filler materials [1][2][3]. The FSW process is somewhat different from other types of welding in that a threaded or nonthreaded pin, installed on a cylindrical tool, approaches the joint line of two butted plates while rotating quickly with a constant spinning speed and is inserted into the plates.…”
Section: Introductionmentioning
confidence: 99%
“…The pin starts to translate along the joint line while still rotating, as shown in Fig. 1 [1][2][3][4][5]. During the welding process, the cylindrical tool is forced down toward the plates to make effective contact between the pin, shoulder, and plate surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations